2009
DOI: 10.1590/s0100-06832009000600032
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of soil structure and porosity under long-term conventional tillage and no-tillage systems

Abstract: Different management systems tend to modify soil structure and porosity over the years. The aim of this study was to study modifications in the morphostructure and porosity of dystroferric Red Latosol (Oxisol) under conventional tillage and no-tillage over a 31-year period. The study began with the description of soil profiles based on the cropping profile method, to identify the most compact structures, define sample collection points for physical and chemical analysis, and determine the water retention curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 15 publications
1
19
0
2
Order By: Relevance
“…These results are in line with Neves et al (2003), Benito et al (2008), Domingos et al (2009) and Tavares Filho & Tessier (2009 and show the differences in soil structure of the two management systems. Conventional tillage of this area with a plow and one or two leveling disk harrows and no-tillage cultivation induced considerable changes in the soil structure between 0 and 0.5 m in comparison to the soil under native forest, with increasingly compacted structures and root growth predominantly in the cracks.…”
Section: Visual Assessment Of Soil Morphologysupporting
confidence: 84%
“…These results are in line with Neves et al (2003), Benito et al (2008), Domingos et al (2009) and Tavares Filho & Tessier (2009 and show the differences in soil structure of the two management systems. Conventional tillage of this area with a plow and one or two leveling disk harrows and no-tillage cultivation induced considerable changes in the soil structure between 0 and 0.5 m in comparison to the soil under native forest, with increasingly compacted structures and root growth predominantly in the cracks.…”
Section: Visual Assessment Of Soil Morphologysupporting
confidence: 84%
“…Tillage systems present great influence in the SPS and consequently in the PSD (Kay and VandenBygaart, 2002;Kravchenko et al, 2011;Peth et al, 2008;Schjønning and Rasmussen, 2000). Tavares Filho and Tessier (2009) observed important changes in the structure of a Brazilian Oxisol induced by conventional (CT) and no-tillage (NT) systems. The authors observed a disaggregated microaggregate structure between 0 and 20 cm for CT and the presence of fissures and biopores for NT.…”
Section: Introductionmentioning
confidence: 99%
“…For the Ch 1 and CT treatments, the low void ratio is attributed to the disruption of soil matrix by soil disturbance with distort pore volume and continuity. Tavares Filho and Tessier () also found lower void ratio from CT treatment than NT system. According to Ribeiro et al.…”
Section: Resultsmentioning
confidence: 85%